Longevity of Aesthetic Fixed Space Maintainers in the Anterior Area of the Pediatric Dental Patient - María Biedma-Perea; Carolina Caleza-Jiménez; Asunción Mendoza-Mendoza; David Ribas-Pérez (MDPI AG, 2023)
Space maintenance for children at very early ages in primary molars or posterior sectors is widely used and the scientific evidence is clear as to its indications. In the anterior sectors there are doubts as to whether there is a loss of space and its use is usually accompanied by aesthetic, phonatory requirements or the completion of certain habits. In this type of aesthetic anterior maintainer, there are many medium and long-term complications that can occur. Purpose: To evaluate the factors determining possible complications capable of reducing the longevity of aesthetic fixed space maintainers placed due to premature loss of temporary upper anterior teeth. Methods: Data were collected on 100 patients of 1-5 years of age requiring fixed space maintainer placement in the upper anterior area due to caries or traumatisms. Results: Complications were recorded in the form of resin tooth fracture (in 41% of the cases), welding fracture (16%), detachments (28%), gingivitis (26%) and root resorptions (8%). Space maintainer placement in younger children (12-24 months of age) was associated with a significantly greater incidence of root resorptions (p < 0.05). Conclusions: Within the limits of the present study, it is concluded that fixed space maintainers would be a good treatment option in patients with prematurely missing anterior teeth, though the use of temporary first molars as abutments could imply a greater risk of failure, with a lesser incidence of root resorptions. Periodic checks and adequate measures of hygiene are essential.